ANALISIS FLUKTUASI HARGA CABAI MERAH KERITING PERIODE JANUARI – DESEMBER 2024 DI PASAR KRAMAT JATI - Muhammad Rizki Fadillah; Riza Fahlapi; Amalia Solehah; Nurlita Widya Ningrum; Sintania Apriliani; Nining Marwati (Universitas Muhammadiyah Gorontalo, 2025)
This study aims to analyze the price fluctuations of curly red chili during the period of January to December 2024 at the Kramat Jati Main Market, East Jakarta. Curly red chili is an important horticultural commodity with high economic value and a direct impact on national food price stability. The research employs a quantitative descriptive method with a statistical analysis approach based on monthly price data. The data used in this study are secondary data obtained from official commodity price reports and supporting scientific references.The results indicate that the price of curly red chili experienced significant seasonal fluctuations. Prices tended to be higher at the beginning and end of the year, while mid-year prices decreased due to increased harvest supply. The mean price of Rp56,566/kg, median of Rp53,710/kg, and mode of Rp55,130/kg suggest that the market remained relatively stable within a medium price range. The quartile, decile, and percentile analyses show considerable price variation with a slightly right-skewed distribution, indicating several periods of high price spikes.The main factors causing price fluctuations include seasonal and weather changes, supply availability, distribution and transportation costs, consumer demand levels, and government policies on food price control. Overall, the findings confirm that curly red chili price fluctuations are seasonal in nature and influenced by complex interactions between supply and demand factors. Price stabilization strategies through production planning, increased storage capacity, and distribution efficiency are necessary to maintain market balance.